The Transformation of Communal Spirituality: A Phenomenological Study of the Sowing of Religious Literacy and Ideology in Tabbae, Benteng Tellue Village, Bone Regency - Nurhalisa Nurhalisa; Wahyuddin Halim; Darmawati H; Nila Sastrawaty; Asrul Muslim (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study highlights the spiritual transformation experienced by the Tabbaqé community, located in Benteng Tellue Village, Amali District, Bone Regency, known as the